Nivel de satisfacción de los clientes en el Centro Deportivo Guaranda Crossfit. - Elizondo Icaza, Oscar Alberto (2022)
Currently the behavior of people, towards a more active and healthy lifestyle that helps them maintain a good immune system to face with serious diseases, has increased greatly, thus making Crossfit an option for these people looking to perform high-intensity physical exercise where you can exercise the whole body in a single session. This case study is carried out with the objective of determining the impact of the deficient infrastructure on the performance of athletes in the Gda Cross sports center in the Guaranda canton, province of Bolivar 2021, following a descriptive analytical methodology, using a survey of athletes who attend to practice this discipline as a tool for data collection of this study, which corresponds and is developed in the research line of information and communication systems, entrepreneurship and innovation and the sub-line of Marketing and Commercialization. Following the proposed methodology, the following problems were identified: there is a reduced physical space that prevents clients from moving around comfortably, the sports equipment is not sufficient for the number of people attending at each schedule, causing scarcity and discomfort among them. All infrastructure problems that have been detected have had a direct influence on the performance of the clients because they do not believe that they have had an increase in their resistance and strength capacity during their training time.